64.2k views
17 votes
How do you solve solving system by substitution can someone give me the steps plz

1 Answer

9 votes

Answer:

Isolate one variable in one of the equations and substituting it into the other equation. *note* in example the first substitution is given to you

Explanation:

For example:

-3x-4y=-2

y=2x-5

Substitute -4y with second equation

-3x-4(2x-5)=-2

PEMDAS

-3x-8x+20=-2

-11x+20=-2

Subtract 20 on both sides of the = sign

-11x=-22

Divide both sides

x=2

Plug that into the second equation

y=2(2)-5

y=4-5

y=-1

User FZE
by
3.9k points